Intercultural Communication of Indian Cultural Dimensions Through Indonesian Secretary’s Perspective - Silintowe, Yunita Budi Rahayu; Susanto, Annie (FISIP Universitas Atma Jaya Yogyakarta, 2018)
The purpose of this research is to analyze the business communication between Indonesian secretaries and expatriate leaders from India in multinational companies. It is a descriptive qualitative research, using interview and FGD. The findings of this reserach, according to Trompenaars’ Cultural Dimensions, shows that the Indian expatriate leaders and Indonesian secretaries have differences in two dimensions, Neutral-Emotional and Achievement-Ascription. If those cultural differences are ignored, they may be potential creating interference in the communication process.